Effects of Adult Aging on Letter Position Coding in Reading: Evidence From Eye Movements - Warrington, Kayleigh L. (Psychol Aging, 2019)
It is well-established that young adults encode letter position flexibly during natural reading. However, given the visual changes that occur with normal aging, it is important to establish whether letter position coding is equivalent across adulthood. In 2 experiments, young (18–25 years) and older (65+ years) adults’ were recorded while reading sentences with words containing transposed adjacent letters. Transpositions occurred at beginning (rpoblem), internal (porblem), or end (problme) locations in words. In Experiment 1, these transpositions were present throughout reading. By comparison, Experiment 2 used a gaze-contingent paradigm such that once the reader’s gaze moved past a word containing a transposition, this word was shown correctly and did not subsequently change. Both age groups showed normal levels of comprehension for text including words with transposed letters. The pattern of letter transposition effects on eye movements was similar for the young and older adults, with greater increases in reading times when external relative to internal letters were transposed. In Experiment 1, however, effects of word beginning transpositions during rereading were larger for the older adults. In Experiment 2 there were no interactions, confirming that letter position coding is similar for both age groups at least during first-pass processing of words. These findings show that flexibility in letter position encoding during the initial processing of words is preserved across adulthood, although the interaction effect in rereading in Experiment 1 also suggests that older readers may use more stringent postlexical verification processes, for which the accuracy of word beginning letters is especially important.